2022
DOI: 10.1002/mrd.23644
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐mediated transgene expression of insulin‐like growth factor 1 in the growth restricted guinea pig placenta increases placenta nutrient transporter expression and fetal glucose concentrations

Abstract: Fetal growth restriction (FGR) significantly contributes to neonatal and perinatal morbidity and mortality. Currently, there are no effective treatment options for FGR during pregnancy. We have developed a nanoparticle gene therapy targeting the placenta to increase expression of human insulin-like growth factor 1 (hIGF-1) to correct fetal growth trajectories. Using the maternal nutrient restriction (MNR) guinea pig model of FGR, an ultrasound-guided, intra-placental injection of non-viral, polymer-based nanop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(73 citation statements)
references
References 50 publications
(90 reference statements)
2
71
0
Order By: Relevance
“…The molecular and physiological mechanisms behind the normalization of Hif1α and Tnfα are yet to be determined, however suggest the ability for the hIGF-1 nanoparticle treatment of the placenta to result in reduced hypoxia in fetal livers. Our analysis of placental morphology with hIGF-1 nanoparticle treatment indicates reduced interhaemal distance between maternal and fetal circulation likely resulting in increased oxygen diffusion 20 , and a possible mechanism by which expression of Hif1α and Tnfα reduced.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The molecular and physiological mechanisms behind the normalization of Hif1α and Tnfα are yet to be determined, however suggest the ability for the hIGF-1 nanoparticle treatment of the placenta to result in reduced hypoxia in fetal livers. Our analysis of placental morphology with hIGF-1 nanoparticle treatment indicates reduced interhaemal distance between maternal and fetal circulation likely resulting in increased oxygen diffusion 20 , and a possible mechanism by which expression of Hif1α and Tnfα reduced.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously shown in the guinea pig MNR model of FGR, efficient uptake of our hIGF-1 nanoparticle gene therapy into the guinea pig placenta, and no transfer of nanoparticle or hIGF-1 plasmid into fetal circulation 20 . In the present study, we aimed to characterize the effects of FGR on hepatic gluconeogenesis gene expression at the initial stages of FGR establishment in the fetal guinea pig, and determine whether treatment of the placenta with our hIGF-1 nanoparticle gene therapy could resolve differences in hepatic gluconeogenesis gene expression in the FGR fetus.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Fetal growth positively correlates with maternal IGF-1 concentrations (Chellakooty, Vangsgaard et al 2004), and both maternal serum levels of IGF-1 and placenta expression of IGF-1R are decreased in FGR (Holmes, Montemagno et al 1997, Laviola, Perrini et al 2005). Additionally, we have previously shown that treatment of the placenta with a non-viral, polymer based, nanoparticle gene therapy that specifically increases human IGF-1 ( hIGF-1 ) in trophoblast, maintains fetal growth in a surgically-ligated FGR mouse model, and increases nutrient transporter expression (Abd Ellah, Taylor et al 2015, Wilson, Owens et al 2020, Wilson, Lampe et al 2021). Placenta treatment with the hIGF-1 nanoparticle does not adversely impact maternal or fetal outcomes, and cannot cross the placenta into fetal circulation (Wilson, Lampe et al 2021, Wilson, Stephens et al 2021).…”
Section: Introductionmentioning
confidence: 99%